Neoliberalism, Resistance, and Self-Limiting Language - Lubienski, Christopher (Education Policy Analysis Archives, 2017)
This discussion offers an overview of the articles and themes developed by the papers in this special issue on Chicago school reform, and also some critical comments on such scholarship. It highlights how these reforms are not organic, as they are often portrayed, but are instead a result of strategic efforts by policymakers and special interests. As the authors of these articles show, these reforms essentially experiment with education “innovations” on poor and minority children in a context where segregation appears to be increasingly accepted. But while the efforts of equity-minded researchers in addressing these issues should be lauded, this discussion goes further and offers some critical commentary on researchers’ use of language, arguing that we too often alienate ourselves from both the policymakers we seek to influence and from the people we seek to help. By adopting exclusive language common in critical theory’s attack on “neoliberalism,” scholars may try to enhance their own credibility by demonstrating familiarity with obscure terminology, but in doing so, may be creating another echo-chamber which excludes them from policy discussions that can effect substantive change.